Historical Perspectives on Thrombolytic Therapy - van de Loo, Jürgen C.W. (Thrombosis and Haemostasis, 1999)
Retrospectives may result in regret over missed opportunities, in grudging acknowledgment of the success of a scientific rival, anger or bemusement about one’s own mistakes, or just plain pride in achievement. Quite apart from these personal implications, it is fascinating to note how a particular medical field has developed, to identify which forces pushed it ahead or slowed it down, to recognize how political and economic influences affected the outcome, and to reflect on the roles that the personalities of responsible scientists played in the process.I would like to comment on the development of basic research on the fibrinolytic system as a prelude to its clinical application, the role of the pharmaceutical industry in producing acceptable drugs, the debate about the pathogenic role of coronary thrombosis in acute coronary syndromes, and finally, on the acceptance and nonacceptance among cardiologists during the infancy and adolescence of the discipline.